2016
DOI: 10.1159/000449011
|View full text |Cite
|
Sign up to set email alerts
|

Pedunculopontine Nucleus Region Deep Brain Stimulation in Parkinson Disease: Surgical Techniques, Side Effects, and Postoperative Imaging

Abstract: The pedunculopontine nucleus (PPN) region has received considerable attention in clinical studies as a target for deep brain stimulation (DBS) in Parkinson disease. These studies have yielded variable results with an overall impression of improvement in falls and freezing in many but not all patients treated. We evaluated the available data on the surgical anatomy and terminology of the PPN region in a companion paper. Here we focus on issues concerning surgical technique, imaging, and early side effects of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 49 publications
2
49
0
Order By: Relevance
“…Therefore, some studies have reported the location of PPN stimulation relative to local landmarks. A detailed discussion on the surgical anatomy and targeting is found in our companion papers . The next 2 issues are raised as important for understanding the medical management of PPN DBS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, some studies have reported the location of PPN stimulation relative to local landmarks. A detailed discussion on the surgical anatomy and targeting is found in our companion papers . The next 2 issues are raised as important for understanding the medical management of PPN DBS.…”
Section: Resultsmentioning
confidence: 99%
“…A detailed discussion on the surgical anatomy and targeting is found in our companion papers. 17,18 The next 2 issues are raised as important for understanding the medical management of PPN DBS.…”
Section: Indicationmentioning
confidence: 99%
“…Many investigators have reported various methods for image acquisition in preparation for DBS surgery. For some structures, such as the pedunculopontine nucleus, there is no consensus on the optimal target site, and therefore it is even more important to devise and introduce targeting methods [3, 4]. …”
Section: Discussionmentioning
confidence: 99%
“…The risk for mortality was lower in the STN DBS group when compared with other DBS targets. However, because the use of non‐STN DBS targets is frequently a second‐line choice when candidates are not optimal for STN DBS including older age, falls, and freezing, the explanation of lower survival in the non‐STN DBS group is likely affected by selection bias. Of note, post‐DBS psychiatric comorbidity was associated with mortality, most likely indicating the negative impact of antipsychotic drugs including worsening of parkinsonism and cardiovascular disease .…”
Section: Univariate and Multivariate Cox Models For Time To Deathmentioning
confidence: 99%
“…To gain insights into the pathogenicity of sHTZ, we therefore examined mitochondrial function and Zn 21 metabolism in skin fibroblasts from sHTZ carriers as described in the Supporting Information and elsewhere. 2,3 When oxygen consumption rate was determined (Fig. 1A), sHTZ cells showed a significant reduction in the maximal respiration and the spare respiratory capacity indicative of impaired mitochondrial respiration (Fig.…”
Section: Mutations Cause Cellular Dysfunction Associated With Parkinsmentioning
confidence: 99%